Four new sesquiterpenoids as natural nitric oxide (NO) inhibitors from the rhizomes of Curcuma phaeocaulis. (December 2015) - Ma, Jiang-Hao; Zhao, Feng; Wang, Ying; Liu, Yue; Gao, Su-Yu; Ding, Li-Qin; Chen, Li-Xia; Qiu, Feng
Graphical abstract: Highlights: Four new guaiane-type sesquiterpenes were isolated from rhizomes of Curcuma phaeocaulis . 13-Norguaiane-type sesquiterpenes were isolated from the genus Curcuma for the first time. Inhibitory effects on nitric oxide production in LPS-activated macrophages were evaluated. Compound1 showed strong inhibitory activity with IC50 value of 3.58 ± 0.17 μ M. Abstract: A new norsesquiterpene named phaeocaulisin N (1 ), and three new guaiane-type sesquiterpenes named phaeocaulisins O–Q (2 –4 ), together with a known norsesquiterpene (5 ) were isolated from the rhizomes of Curcuma phaeocaulis . Their structures were established based on extensive spectroscopic analysis. Compounds1 and5, as far as we know, are the first example of 13-norguaiane-type sesquiterpenes isolated from the genus Curcuma . All of the isolated compounds were tested for inhibitory activity against LPS-induced nitric oxide production in RAW 264.7 macrophages. Compound1 showed strong inhibitory activity on nitric oxide production with IC50 value of 3.58 ± 0.17 μM.